Comparison of serum lipid management between elderly and non-elderly patients with and without coronary heart disease (CHD) - Shimizu, Rumiko (Prev Med Rep, 2016)
Serum lipid management in patients aged ≥ 75 has not been precisely explored. We, therefore, compared the serum lipid management between the two age groups with and without coronary heart disease (CHD). We, therefore, retrospectively reviewed medical charts of patients who were hospitalized in the departments of internal medicine during a period of 14 months. Serum lipid goal attainment was explored by applying the lipid goals for patients aged < 75 to those aged ≥ 75. In 1988 enrolled patients, 717 subjects (36.1%) were aged ≥ 75. Among them, 41.3% and 32.4% of the patients had CHD, 44.2% and 41.0% were primary prevention at high-risk, and 14.5% and 14.6% were primary prevention at moderate-risk in patients aged ≥ 75 and aged < 75, respectively. Serum LDL-C goal achievement rates in CHD were 66.9% and 65.0% in patients aged ≥ 75 and < 75, respectively (p = 0.334). In the primary prevention at high-risk, these rates were 73.5% and 63.3%, in patients aged ≥ 75 and < 75, respectively (p = 0.001). They were 77.9% and 58.1% in primary prevention at moderate-risk aged ≥ 75 and < 75, respectively (p < 0.001). In CHD, lipid-lowering medication subscription rates were significantly lower in patients aged ≥ 75 (60.1%) than those aged < 75 (73.8%, p < 0.001). In conclusion, in CHD, serum lipid goal attainment was comparable between the two age groups although the lipid-lowering drugs were less frequently prescribed in patients aged ≥ 75. Without CHD, it was significantly better in patients aged ≥ 75 than those aged < 75 although the lipid-lowering drug subscription rates were comparable between the two age groups.